Around Malaysia / Siti Hajar Ahmad Zahir … [et al.] - Ahmad Zahir, Siti Hajar; Mohamad Zaid, Nur Ainami; Mohamad Sapandi, Siti Nur Amirah; Shakor, Khairun Aida Shahirah (2022)
Tourism and technology have emerged as significant areas with the ability to contribute to economic growth. The app is intended to guide visitors to fascinating spots in Malaysia. This app is called "A/M App” that stand for Around Malaysia travel application. This app is available downloaded at google play store and Appstore. This software is intended to make it easier for travelers to visit fascinating spots in Malaysia. This app is quite useful for foreign travelers who are participating in tourism activities in Malaysia. Next, the primary goal of developing this application is to provide more thorough information about places of interest in Malaysia to visit. Furthermore, the findings of this study revealed that 30 respondents agreed to utilize this application to help users identify sites of interest throughout Malaysia. As a recommendation, hopefully, this app is constantly updated with information on new and interesting places to visit.